2018
DOI: 10.17509/ijal.v8i2.13308
|View full text |Cite
|
Sign up to set email alerts
|

Vocational school EFL teachers’ practices of integrating ICT into English lessons: Teachers’ voices

Abstract: Despite numerous studies on ICT-ELT integration, little is known about how English teachers in vocational schools in Asia and particularly in Indonesia integrate ICT into their English lessons. To fill this gap, this study aims to investigate how vocational English teachers integrate ICT into their English teaching practices in vocational high school settings. It specifically examines vocational high school English teachers’ reasons for using ICT, the ways the English teachers integrate ICT into their English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 14 publications
3
23
0
3
Order By: Relevance
“…Penelitian tentang praktik guru bahasa Inggris dalam pemanfaatan teknologi sudah pernah di teliti oleh beberapa peneliti seperti Rodliyah (2018) yang menginvestigasi bagaimana guru di sekolah kejuruan memanfaatkan teknologi ke dalam praktik pembelajaran di kelas bahasa Inggris. Dalam penelitiannya tersebut, Rodliyah (2018) menemukan bahwa para guru memanfaatkan teknologi dengan beragam alasan, seperti ketertarikan guru dalam menggunakan teknologi, tuntutan masa kini, membutuhkan manfaat dari teknologi dan juga karena guru merasa percaya diri ketika mengintegrasikan pelajaran bahasa Inggris dengan teknologi. Berbeda dengan (Hakkarainen et al, 2001;Rodliyah, 2018) menganalisis hubungan antara kemampuan guru dalam menggunakan perangkat teknologi, pemikiran pedagogis guru, dan laporan individu guru dalam praktik pemanfaatan teknologi di dalam kelas.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian tentang praktik guru bahasa Inggris dalam pemanfaatan teknologi sudah pernah di teliti oleh beberapa peneliti seperti Rodliyah (2018) yang menginvestigasi bagaimana guru di sekolah kejuruan memanfaatkan teknologi ke dalam praktik pembelajaran di kelas bahasa Inggris. Dalam penelitiannya tersebut, Rodliyah (2018) menemukan bahwa para guru memanfaatkan teknologi dengan beragam alasan, seperti ketertarikan guru dalam menggunakan teknologi, tuntutan masa kini, membutuhkan manfaat dari teknologi dan juga karena guru merasa percaya diri ketika mengintegrasikan pelajaran bahasa Inggris dengan teknologi. Berbeda dengan (Hakkarainen et al, 2001;Rodliyah, 2018) menganalisis hubungan antara kemampuan guru dalam menggunakan perangkat teknologi, pemikiran pedagogis guru, dan laporan individu guru dalam praktik pemanfaatan teknologi di dalam kelas.…”
Section: Pendahuluanunclassified
“…Dalam penelitiannya tersebut, Rodliyah (2018) menemukan bahwa para guru memanfaatkan teknologi dengan beragam alasan, seperti ketertarikan guru dalam menggunakan teknologi, tuntutan masa kini, membutuhkan manfaat dari teknologi dan juga karena guru merasa percaya diri ketika mengintegrasikan pelajaran bahasa Inggris dengan teknologi. Berbeda dengan (Hakkarainen et al, 2001;Rodliyah, 2018) menganalisis hubungan antara kemampuan guru dalam menggunakan perangkat teknologi, pemikiran pedagogis guru, dan laporan individu guru dalam praktik pemanfaatan teknologi di dalam kelas. Sementara itu, Rollins (2011) mengobservasi kelas taman kanak-kanak hingga kelas 5 SD di sekolah negeri untuk menemukan perbedaan praktik pembelajaran dalam pemanfaatan teknologi oleh guru.…”
Section: Pendahuluanunclassified
“…A study confirmed that senior high school teachers reported that they are knowledgeable in integrating ICT in their classroom even when teaching in rural schools [57]. However, junior high school teachers were not as knowledgeable as those of senior high schools on the use of ICT in teaching [58], [59]. A similar conclusion can be made for elementary school teachers [60].…”
Section: Discussionmentioning
confidence: 71%
“…Paprocki (2016) in Ślusarczyk (2018) added that there are three important points in the 4th Industrial Revolution era is (1) an era of common digitization and ensuring constant communication, (2) an era of disruptive innovations, (3) and an era of development of autonomous machines and the use of artificial intelligence in the process of their control. Rodliyah (2018) explained that the rapid advancement of information and communication technology (ICT) has brought about some changes in almost all aspects of our life, including education in general and ELT in particular. While Chun, Kern, & Smith in Rodliyah (2018) added that this is because technology offers easy access to different people, languages, cultures, and social practices The importance of English Communicative Competence is stated by Rickheit and Strohner in Rochim (2019) that the ability to reach people goals in social life depends on their communicative competence.…”
Section: Introductionmentioning
confidence: 99%
“…Rodliyah (2018) explained that the rapid advancement of information and communication technology (ICT) has brought about some changes in almost all aspects of our life, including education in general and ELT in particular. While Chun, Kern, & Smith in Rodliyah (2018) added that this is because technology offers easy access to different people, languages, cultures, and social practices The importance of English Communicative Competence is stated by Rickheit and Strohner in Rochim (2019) that the ability to reach people goals in social life depends on their communicative competence. It means that people communication is important and people must have competence to be communicative.…”
Section: Introductionmentioning
confidence: 99%